BAWDI: THE ELOQUENT EXAMPLE OF HYDROLIC ENGINEERING AND ORNAMENTAL ARCHITECTURE - Pandey, Anjali (International Journal of Research -GRANTHAALAYAH, 2016)
“The secular Indian architecture includes town planning, palaces, general houses and forts of various categories. There was a constant growth in forms of this architecture from the period of harappan culture up to the Vijaynagar epoch. The towns were protected by walls (prakara) and the moats parikha. Each town provided places of general public utility, such as temples, stupas, schools, hospitals, markets, gardens and ponds”.1